Investigation of Masking Thresholds for Spatially Distributed Sound Sources - Dick, Sascha; Sweidan, Rami; Herre, Jürgen (147th Audio Engineering Society International Convention 2019, 2019)
For perceptual audio coding of immersive content, the investigation of masking effects between spatially distributed sound sources is of interest. We conducted subjective listening experiments to determine the masking thresholds for ‘tone-masking-noise’ conditions when masker (1 kHz sine tone) and probe (1 kHz narrow band noise) are spatially distributed, using an immersive 22.2 loudspeaker setup. Our results show masking thresholds in the range of -35 dB to -26 dB probe-to-masker-ratio. As expected, least masking was found between left/right opposed sources with up to 5 dB lower than for coincident sources. Other noteworthy observations included an increase of masking for certain elevations and cases of selective masking decrease due to interaural phase difference phenomena.
herre_papers_perception_and_perception_based_signal_processing